Geotechnical Investigation on Soil Properties Influencing the Swelling Characteristics of Expansive Soil - Hashish, Saleh M. S. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Expansive soil which can be found in the semi-arid climates are considered to be one of the natural hazards due to its potential to change in volume when exposed to variations of moisture condition causing wetting and drying of the soil. These volume changes in soils affect the soil’s engineering behavior causing serious structural damages for the light-weight structures above. The swelling of expansive soils is mostly affected by the vertical surcharge applied on the soil during saturation. In this experimental study, the effect of soil properties such as initial moisture content, dry density, applied surcharge, and pore fluid chemistry on the swelling behavior of expansive soil were studied and the effect of pore fluid chemistry on soil suction was discussed. In order to examine the one-dimensional swelling behavior of the expansive soil, specimens were compacted at different dry density values (1.18, 1.5, 1.6, and 1.82 g/cm3 ) and mixed with different initial moisture contents (12%, 14%, and 16 %) under applied vertical stresses (0, 7, and 15 kPa). Moreover, soil suction test was performed using filter paper method considering different initial moisture contents (5%, 7%, 9%, 12%, 14%, 19%, and 20%). Measurement of soil suction by contact and non-contact filter paper placement method was applied to measure the matric and total suction values, respectively and then the soil-water characteristics curve of the expansive soil were drawn. This study concluded that the increase of initial moisture content resulted in overall reduction of percent swelling and swelling coefficient in both primary and secondary swelling phases which resulted from the lack of empty pore spaces in the already water filled soil pores. The influence of increasing dry density showed a threshold value of 1.6 g/cm3 . Percent swelling increased at lower water content values below the threshold value and decreased at higher water content and dry density above the threshold value. Applying surcharge pressures restricted the uplift movement and resulted in lower swelling values for all cases. The obtained results indicated that mixing the soil with the seawater caused changes in the diffused double layer (DDL) thickness due to the reaction between the soil particles and the seawater. The compressed double layer generated a soil with a soil texture similar to the coarse texture and caused a significant reduction in soil particles water holding capacity. This resulted in a decrease in the swelling potential. Suction measurements of the soils mixed with distilled water and the seawater indicated a significant increase in the osmotic suction values of the soil mixed with the seawater. The air entry value, AEV of the soil mixed with the seawater had a lower AEV (92.35 kPa) than the soil mixed with distilled water (354.35 kPa) which was due to the weakened water storing capacity of the soil mixed with the seawater. Lower AEV of the soil mixed with the seawater indicated that higher pressure was needed for air to enter into the soil pores of the specimens mixed with distilled water.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2021. Supervisor: Prof. Dr. Zalihe Nalbantoğlu Sezai.
Keywords: Civil Engineering Department; Soil Mechanics--Soils--Liquefaction; Air entry value, diffuse double layer, expansive soil, flocculation, suction, swelling